Trypanocidal Activity of Oxoaporphine and Pyrimidine-β-Carboline Alkaloids from the Branches of Annona foetida Mart. (Annonaceae) - Celso Vataru Nakamura; Benedito Prado Dias Filho; Rodrigo Hinojosa Valdez; Tânia Ueda-Nakamura; Francinete Ramos Campos; Andersson Barison; Afonso Duarte Leão de Souza; Emmanoel Vilaça Costa; Maria Lúcia Belém Pinheiro (Molecules, 2011)
Phytochemical investigation of the branches of Annona foetida Mart. led to isolation from the CH2Cl2 extract of four alkaloids: Atherospermidine (1), described for the first time in this species, liriodenine (2), O-methylmoschatoline (3), and annomontine (4). Their chemical structures were established on the basis of spectroscopic data from IR, MS, NMR (1D and 2D), and comparison with the literature. Compounds 2–4 showed potent trypanocidal effect when evaluated against epimastigote and trypomastigote forms of Trypanosoma cruzi.